Eosinophils and temperature in the postoperative period - Ramírez del Villar, Eduardo (1952)
In 36 patients who were to be operated, has been tested on test Adrenaline as performance index of the anterior hypothalamus-pituitary-adrenocortical before and after system operation. Furthermore, we have studied the behavior of daily blood eosinophils during postoperative period, temperature related. The Adrenaline Test has been very inconsistent without diagnostic value of functional status before hypothalamus-pituitary-adrenocortical system. For this reason, the test has no prognostic value indicative of the resistance of patients to surgery. Instead, the constant and regular numerical variations of blood eosinophils - opposed to the thermocline - do recommend the routine use of Direct eosinophil count in the postoperative period. Both to control the patient's general condition, the early to discover any possible complications. Four patients with eosinophilia pulmonary echinococcosis were operated not follow the normal numerical variations of blood eosinophils in the second phase of the post-operative period.